Discriminación económica de género en los egresados de administración y finanzas de Los Mochis, Sinaloa (Gender economic discrimination in administration and finance graduates from Los Mochis, Sinaloa) - Guerra, E.; Vargas Hernández, José G.; Robles, N. (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. In this documents is described the gender discrimination of the administration gradutes, 1999-2003 generation from Universidad de Occidente (U de O) in Los Mochis. In general terms the average of incomes has no difference on the gender, mainly due to the high standard deviation of individual incomes. The income differences can not be explained neither by the family dimension such as marital status, nor the number of children, nor the working condition, nor the educational degree for the parents or spouse; nor by the educational dimension, but by the occupational dimension. Gender discrimination is due to the labour market’s segmentation that is, there are jobs destined to a single gender. The exclusive jobs for female administrator are in the category of under employment; whereas those for males have higher average of income.